Nostalgia and Heroism: Theoretical Convergence of Memory, Motivation, and Function - Allison, Scott T.; Green, Jeffrey D. (Frontiers in Psychology, 2020)
This article seeks to develop theoretical convergences between the science of nostalgia and the science of heroism. We take four approaches in forging a conceptual relationship between these two phenomena. First, we examine the definitions of nostalgia and heroism from scholars, laypeople, and across cultures, noting how the history of defining the two phenomena has shaped current conceptualizations. Second, we demonstrate how nostalgic experiences consist of reminiscences about our own personal heroism and about cultural role models and heroes. A review of heroism research, moreover, shows also that our recall of our heroes and of heroism is tinged with nostalgia. Third, we make linkages between heroism and nostalgia research focusing on functions, inspiration, sociality, and motivation. Nostalgia researchers have illuminated the functions of nostalgia implicating the self, existential concerns, goal pursuit, and sociality. Our review shows that heroism researchers invoke similar categories of hero functionality. Finally, we propose three areas of future research that can profit from the merging of nostalgia and heroism science, involving the mechanisms by which (a) heroism can fuel nostalgia, (b) nostalgia can promote heroic action, and (c) wisdom results from nostalgic reverie.